A COMPARATIVE STUDY OF ENTREPRENEURSHIP IN DEVELOPED AND DEVELOPING COUNTRIES: A SYSTEMATIC LITERATURE REVIEW - Rama, Rovanita; Zulaika, Siti (Bussman Journal : Indonesian Journal of Business and Management, 2025)
This study presents a systematic analysis of 20 Scopus-indexed journal articles comparing the nature and dynamics of entrepreneurship in developed and developing countries. The research explores the key dimensions of entrepreneurial motivation, institutional and policy environments, access to finance and technology, education and human capital, and prevailing challenges and barriers. Findings indicate that entrepreneurship in developed countries is predominantly opportunity-driven, supported by strong institutions, innovation ecosystems, and access to finance and education. Conversely, entrepreneurship in developing countries tends to be necessity-driven, constrained by limited resources, weak policy frameworks, and inconsistent access to capital and technology. Nevertheless, digitalization and globalization are fostering a degree of convergence, offering new opportunities for developing nations to enhance competitiveness through technology adoption and education reform. The study concludes that entrepreneurship is context-dependent—shaped by socio-economic structures, institutional quality, and human development levels. Policymakers are urged to design tailored strategies that strengthen entrepreneurial ecosystems, promote innovation, and bridge gaps in finance, education, and infrastructure to support sustainable and inclusive growth.